2020
DOI: 10.3389/fimmu.2020.00832
|View full text |Cite
|
Sign up to set email alerts
|

Engineered IL-21 Cytokine Muteins Fused to Anti-PD-1 Antibodies Can Improve CD8+ T Cell Function and Anti-tumor Immunity

Abstract: Inhibitors that block the programmed cell death-1 (PD-1) pathway can potentiate endogenous antitumor immunity and have markedly improved cancer survival rates across a broad range of indications. However, these treatments work for only a minority of patients. The efficacy of anti-PD-1 inhibitors may be extended by cytokines, however, the incorporation of cytokines into therapeutic regimens has significant challenges. In their natural form when administered as recombinant proteins, cytokine treatments are often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 51 publications
0
45
0
Order By: Relevance
“…[ 59 ] IL‐21 has also been fused with PD‐1 blocking antibodies, demonstrating treatment efficacy in humanized cancer models refractory to anti‐PD‐1 monotherapy. [ 60 ] Here, treatment‐associated tumor control and CD8 + T‐cell cytolytic activity were superior to anti‐PD‐1 therapy alone, with comparable levels of PD‐1 inhibition.…”
Section: Immunostimulatory Cytokinesmentioning
confidence: 97%
“…[ 59 ] IL‐21 has also been fused with PD‐1 blocking antibodies, demonstrating treatment efficacy in humanized cancer models refractory to anti‐PD‐1 monotherapy. [ 60 ] Here, treatment‐associated tumor control and CD8 + T‐cell cytolytic activity were superior to anti‐PD‐1 therapy alone, with comparable levels of PD‐1 inhibition.…”
Section: Immunostimulatory Cytokinesmentioning
confidence: 97%
“…Recently two independent reports showed that targeting IL-21 directly to T cells rather than systemic delivery in combination with PD-1 therapy improved tumor immunity. They also showed that systemic delivery of soluble IL-21 did not improve the therapeutic efficacy of PD-1 blockade, however when the anti-PD-1 antibody was fused to IL-21 synergetic improvement in tumor immunity was noticed (139,140). There are currently many efforts to translate the use of single and combinations of these cytokines to expand TIL and CAR products for ACT, as well as novel ways to incorporate cytokine releasing switches in CAR constructs and fusion proteins.…”
Section: Cytokine Priming and Metabolic Re-programmingmentioning
confidence: 99%
“…On another hand, IL-21 might also become toxic for lymphomas by expanding and enhancing tumour-infiltrating cytotoxic CD8 + cells and NK cells [ 163 , 164 , 165 , 166 ]. Such immunotherapeutic potential of IL-21 to stimulate anti-tumour immune responses is being clinically investigated in different cancers [ 160 , 167 , 168 ].…”
Section: The Pd-1/pd-l1 Axis In Dlbclmentioning
confidence: 99%
“…Antibody-cytokine conjugated proteins represent another class of biopharmaceuticals in cancer immunotherapy [ 201 ]. Combination therapy of IL-21 with PD-1 or CTLA-4 previously showed efficacy in mouse tumour models [ 202 ], and an engineered IL-21 fused to a PD-1 antibody showed promising results by providing superior anti-tumour immunity than anti-PD-1 alone in preclinical studies [ 167 ].…”
Section: Immunotherapy Perspectives In Dlbclmentioning
confidence: 99%